Gaining, Losing, and Regaining Merit-Based Scholarships - David C. Ribar; Ross Rubenstein (Institute of Labor Economics (IZA), 2021)
Georgia offers two merit-based scholarships to in-state college students: HOPE Scholarships, which provide partial tuition support, and Zell Miller Scholarships, which provide full tuition support but with more stringent eligibility and retention conditions. Studies have examined retention of these scholarships but not other dynamics, including gaining HOPE Scholarships if students enter without them and follow-on transitions after students initially lose or gain a scholarship. This study uses 2013-2019 administrative data from 26 University System of Georgia institutions to jointly estimate multivariate competing-risk hazard models of a) losing an entering Zell Miller Scholarship, b) losing an entering HOPE Scholarship, c) gaining a HOPE Scholarship after matriculating without one, d) regaining a scholarship, and e) losing a non-entering scholarship. Many students change their scholarship status-event-history analyses predict that 25 percent of entering Zell Miller Scholarship students lose their scholarships by their 90th credit hour, 42 percent of entering HOPE Scholarship students lose their scholarship by their 90th credit hour, and 27 percent of students who enter without a scholarship gain them. Students of color, students with economic disadvantages, and men are more likely to lose scholarships and less likely to gain scholarships. These dynamics compound inequities in initial scholarship receipt.
Keywords: I22; 330; dynamics; equity; financial aid; administrative data; merit-based scholarships